2012
DOI: 10.1590/s0102-33062012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Análise cromossômica em bulbilhos de sisal (Agave spp.) cultivados em diferentes municípios baianos, Brasil

Abstract: O plantio de sisal tornou-se uma das atividades econômicas mais importantes na região do semiárido baiano, onde as adversidades ambientais impedem o plantio de outras culturas. Diante da importância econômica, estudos de citogenética são necessários, pois podem fornecer informações que auxiliem na produção de linhagens melhoradas. A análise de bulbilhos, coletados de cinco localidades diferentes da Bahia, mostrou a presença de indivíduos diplóides e pentaplóides, com comprimento cromossômico variando de 24,56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…IAC4 may be a remnant line of the IAC hybridization experiments conducted in 1958 (Salgado et al, 1979). Also, A. amaniensis is diploid (2n = 60) unlike A. sisalana (Doughty, 1936;Queiroz et al, 2012), and recent chloroplast analysis has also shown that these two species are not the same (Xu et al, 2022). From a morphophysiological perspective, the IAC1, IAC3, and IAC4 samples showed contrasting behaviors when compared to A. sisalana, particularly in terms of chlorophyll content (Figure 6B).…”
Section: Using Mayahuelin To Trace the History Of Agave Accessions In...mentioning
confidence: 94%
See 1 more Smart Citation
“…IAC4 may be a remnant line of the IAC hybridization experiments conducted in 1958 (Salgado et al, 1979). Also, A. amaniensis is diploid (2n = 60) unlike A. sisalana (Doughty, 1936;Queiroz et al, 2012), and recent chloroplast analysis has also shown that these two species are not the same (Xu et al, 2022). From a morphophysiological perspective, the IAC1, IAC3, and IAC4 samples showed contrasting behaviors when compared to A. sisalana, particularly in terms of chlorophyll content (Figure 6B).…”
Section: Using Mayahuelin To Trace the History Of Agave Accessions In...mentioning
confidence: 94%
“…The limited applicability of the Mayahuelin marker in A. sisalana may be attributed to the origin of this species. A. sisalana is an irregular pentaploid (2n = 5x = 149) (Queiroz et al, 2012) and believed to be a hybrid, possibly between A. angustifolia and A. kewensis (Gentry, 1982), although this has not been yet confirmed. This complex genome composition increases the likelihood of off-target amplification during PCR, and since there is no control over which copy of the gene will be amplified due to polyploidy, it can result in varying outcomes in phylogenetic inference.…”
Section: Using Mayahuelin To Trace the History Of Agave Accessions In...mentioning
confidence: 99%
“…Possui um caule curto, situado ao nível do solo, folhas longas, suculentas, rígidas, convexas e de coloração verde opaca, inseridas diretamente no caule. Com elevada capacidade de armazenar água e nutrientes, é constituída de uma camada externa de epiderme espessa e resistente, que a protege contra as condições adversas de ambientes áridos (SILVA, 1999;QUEIROZ et al, 2012). Trata-se de uma planta bastante resistente às pressões ambientais, capaz de sobreviver em ecossistemas variados, em climas com baixa umidade e altas temperaturas, tornando-a ideal para o cultivo em regiões tropicais (VIEIRA; FILHO, 2021).…”
Section: Introductionunclassified
“…Originally from the Yucatan Peninsula in Mexico, sisal was exported to Brazilian territory during the 19th century [1]. Nowadays, sisal is crucial for the socioeconomic development of the semi-arid region of the northeast region, particularly in the state of Bahia, which accounts for 90% of its production [2]. Brazil is currently the world's largest producer of sisal, with an average annual production of approximately 140 thousand tons of its hard fiber [3][4][5].…”
Section: Introductionmentioning
confidence: 99%